Development of the cascading module for hydro energy decision support system (HEDSS) for Temenggor-Bersia-Kenering power plants - Nadzri, Ezuria (2002)
Reservoir operation has generate electric power for Tenaga Nasional Berhad for a few decades now, yet the solution to ease daily operation in making decision pertaining to the power optimization remain problematic. Despite development of new techniques, implicit stochastic optimization models using linear programming (LP) remain one of the most readily applicable to the analysis of complex system. However, optimization calculation using manual approach consumes ample of time. This dissertation presents the development of an automation system (HEDSS) to ease the optimization calculation. The scope however is limited to the cascading module. The proposed method is implemented using Waterfall model of System Development Life Cycle (SDLC). The power plants chosen were Temengor, Kenering, Bersia; three cascading reservoirs at Sg.Perak. The method is demonstrated by comparing approach done manually versus automation. The objective function is to minimized the economic cost in hydropower plants operations. A generalized network flow algorithm is used to find the optimal solution.